Residual Stress in Friction Stir Welding of Dissimilar Aluminum Alloys: A Parametric Study - Sarfaraz, Zulqarnain; Awan, Yasser Riaz; Saeed, Hasan Aftab; Khan, Rehan; Wieczorowski, Michał; Din, Naveed Akmal (Materials, 2025)
Welding-induced residual stress has the capacity to significantly compromise the integrity of mechanical components. Its minimization therefore plays a critical role in the selection of process parameters during the welding process. Friction stir welding is a useful joining technique to weld many materials that are not amenable to the traditional welding techniques. Using a sequentially coupled thermomechanical three-dimensional finite element simulation, this work aimed to quantitatively evaluate the influence of the tool rotational and traverse speeds on the generation of residual stress in the friction stir welding of dissimilar aluminum alloys AA2024−T3 and AA5086−O. The model was validated using established experimental and numerical results. The procedure entailed an initial thermal analysis, the results of which were superposed on a mechanical model to determine the distribution of the residual stress across the welded alloy. The results showed that longitudinal residual stress was dominant as compared to lateral stress. It was also demonstrated that, although the tool rotational speed and the tool traverse speed both affected the post-weld temperature distribution and consequently the longitudinal residual stress, the influence of the former was more substantial. Furthermore, the peak values of the residual stress were found on the retreating side (AA5086−O), making it more critical for the selection of welding process parameters.